β-Site amyloid precursor protein–cleaving enzyme 1 activity is related to cerebrospinal fluid concentrations of sortilin-related receptor with A-type repeats, soluble amyloid precursor protein, and tau - Tsolakidou, Amalia; Alexopoulos, Panagiotis; Guo, Liang-Hao; Grimmer, Timo; Westerteicher, Christine; Kratzer, Martina; Jiang, Meizi; Bujo, Hideaki; Roselli, Francesco; Leante, Maria Rosaria; Livrea, Paolo; Kurz, Alexander; et al. (Alzheimer's & dementia, 2013)
Abstract Background β-Site amyloid precursor protein (APP)–cleaving enzyme 1 (BACE1) activity determines the rate of APP cleavage and is therefore the main driver of amyloid β production, which is a pathological hallmark of Alzheimer’s disease (AD). Methods The present study explored the correlation between BACE1 activity and cerebrospinal fluid (CSF) markers of APP metabolism and axonal degeneration in 63 patients with mild AD and 12 healthy control subjects. Results In the AD group, positive correlations between BACE1 activity and soluble APP β, the APP sorting receptor sortilin-related receptor with A-type repeats (also known as SorLA or LR11), and tau were detected. BACE1 activity was not associated with amyloid β1–42 or soluble APP α concentrations in the AD group, and no associations between BACE1 activity and any of the protein concentrations were found in the control group. Conclusion Our results confirm the relevance of BACE1 and sortilin-related receptor with A-type repeats within the amyloid cascade and also provide a further piece of evidence for the link between amyloid and tau pathology in AD.